Aspectos da produção de mudas de óleo elétrico (Piper callosum) por estaquia (Revista Brasileira de Plantas Medicinais, 2025)
Several factors can influence the success of vegetative propagation, such as light intensity, substrate, temperature, humidity, cutting length and the presence of leaves and buds. The substrate should provide good support, moisture retention and sandblasting for the development of roots. The objective of this study was to investigate the length of pegs and ideal substrates for obtaining uniform and vigorous of Piper callosum seedlings. In addition, morfoanatomic study was initiated on the physiological species plasticity. The experiment was held in a randomized block design in a factorial with 3 substrates: 1) sand, 2) soil: sand, 3) soil: sand: organic compost) x 3 stakes sizes: 100 mm, 200 mm, 300 mm, with four replicates per treatment. Growth data analysis of the seedlings were subjected to analysis of variance and Tukey test using the program Sisvar. The results showed that the best long stakes for this species, was 200 mm and the soil substrate: sand: compost offered the best conditions for the development of seedlings.